Improvement of Bacterial Vaginosis by Oral Lactobacillus Supplement: A Randomized, Double-Blinded Trial - Ta-Chin Lin; I-Ling Hsu; Wan-Hua Tsai; Yi-Chih Chu; Lung-Ching Kuan; Min-Syuan Huang; Wen-Ling Yeh; Ya-Hui Chen; Shan-Ju Hsu; Wen-Wei Chang (Applied Sciences, 2021)
Bacterial vaginosis (BV) is the most common vaginal infection globally, with a high recurrent rate after antibiotic treatment. Probiotics consumption is known to improve BV with different efficacy among species or strains. After in vitro selection of Lactobacillus strains with growth inhibition and preventing adhesion to HeLa cervical epithelial cells, a randomized and double-blinded trial of two Lactobacillus formula, namely, VGA-1 and VGA-2, in BV patients with Nugent scores of 4–10 was conducted. Among 37 subjects who completed the trial, we observed significantly decreased Nugent scores in both VGA-1 (n = 18) and VGA-2 (n = 19) consumption groups. VGA-1 consumption significantly improved vaginal discharge odor/color and itching at both 2-week and 4-week-consumption, but those only observed after a 4-week-consumption in the VGA-2 group. We also observed a tendency to reduce recurrent rates among enrolled participants after VGA-1 or VGA-2 consumption. The improvement effect of VGA-1/VGA-2 was associated with the significant reduction of interleukin-6 expression after 4-week-consumption and the restoration of normal vaginal microflora by quantitative polymerase chain reaction analysis. In conclusion, VGA-1 or VGA-2 displayed beneficial effects in BV patients, but the VGA-1 formula showed a better efficacy, potentially used for BV intervention.